2013
DOI: 10.1111/jbl.12008
|View full text |Cite
|
Sign up to set email alerts
|

Take This Job and Shove It: Examining the Influence of Role Stressors and Emotional Exhaustion on Organizational Commitment and Identification in Professional Truck Drivers

Abstract: P rofessional truck drivers experience many challenges in the course of performing their jobs. Drivers must meet the needs of their company, shippers, and receivers as well as comply with safety regulations. It is well documented that truck drivers are prone to physical exhaustion; however, they may also be subject to emotional exhaustion, which can impact their decision to remain with a company. This research examines the influence of job stressors, such as role conflict and role ambiguity and their relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 67 publications
6
71
0
Order By: Relevance
“…; Kemp et al. ). As mentioned above, SET provides a theoretical framework to understand the relationship between the servant leader and the follower, whereby followers, as a result of the leader's selfless acts, develop a greater level of commitment to the organization.…”
Section: Hypothesesmentioning
confidence: 98%
“…; Kemp et al. ). As mentioned above, SET provides a theoretical framework to understand the relationship between the servant leader and the follower, whereby followers, as a result of the leader's selfless acts, develop a greater level of commitment to the organization.…”
Section: Hypothesesmentioning
confidence: 98%
“…Additionally, client/host identified challenges also have the potential to lead to innovation through joint efforts. Employees who are committed to an organization are typically willing to exert extra effort (Kemp et al 2013). These boundary spanners who are committed to their host firms are likely to actively seek ways to improve logistics processes between the firms through the identification and development of innovative approaches.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Avanzi et al (2015) report that organizational identification negatively affects emotional exhaustion and reduced personal accomplishment. In addition, Kemp et al (2013) have found a negative and significant relationship between organizational identification and emotional exhaustion, and Wegge et al (2006) and Lammers et al (2013) verify that organizational identification negatively and significantly affects emotional exhaustion and depersonalization. In addition, Wegge et al (2006) clarify the positive relationship between organizational identification and personal accomplishment.…”
Section: Theoretical Implicationsmentioning
confidence: 83%